Bipolar Pythagorean neutrosophic Hamacher Heronian mean operators: a framework in MCDM / Nur Fathiah Fatin Mohamad Fauzi, Zahari Md Rodzi and Norzieha Mustapha - Mohamad Fauzi, Nur Fathiah Fatin; Md Rodzi, Zahari; Mustapha, Norzieha (Universiti Teknologi MARA, Perak, 2025)
This paper aims to overcome existing limitations in multi-criteria decision-making (MCDM) framework by integrating Bipolar Pythagorean Neutrosophic Set (BPNS) with advanced aggregation operators specifically the Hamacher and the Heronian mean. These integrations are designed to enhance the effective representation and synthesis of decision criteria. To achieve this, a novel framework, the bipolar pythagorean neutrosophic set-generalized Hamacher Heronian mean (BPNS-GHHM) has been proposed. The proposed method satisfies all properties and demonstrates its effectiveness in solving complex MCDM problems.